Analisis Kesehatan Bank Pada Perusahaan Bank BUMN Periode 2018 – 2022 - Achmad Hamka Hamid; Anwar Ramli; Nurman; Anwar; Annisa Paramaswary Aslam (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research aims to determine the health level of state-owned banks for the period 2018 – 2022. The tool used to measure the health level of banks is the CAMEL (Capital, Asset, Management, Earnings, and Liquidity) analysis. The population of this research is 3 (three) state-owned banks listed on the Indonesia Stock Exchange (BEI), namely BRI, BNI, and Mandiri. The data used are financial reports from the three banks for the period 2018 - 2022. The results of this research show that in general the best financial performance is obtained by BRI, followed by Mandiri, and third is BNI and has the HEALTHY predicate. This is shown by the highest CAR, KAP, NIM, ROA, BOPO and LDR ratio values obtained by BRI, followed by Mandiri and the lowest is BNI. In general, the CAMEL score can illustrate that state-owned bank for the 2018 - 2022 period are quite good in terms of their financial performance and maintaining the bank's health level.